Implementasi Model Kooperatif Tipe TGT Berbantu Cardopoly Clue untuk Meningkatkan Hasil Belajar - Ramadhanty, Aisyah Nestria Al Falah; Jatmiko; Lestari, Dwi Puji (Cipta Media Harmoni, 2025)
Efforts to improve science learning outcomes with the help of Cardopoly Clue media were carried out because there were still 13 out of 24 students who had scores below 75 or the Learning Objective Achievement Criteria (KKTP). The purpose of this study was to improve the science learning outcomes of grade 5 students of Pojok 1 Elementary School by implementing the TGT type cooperative model assisted by Cardopoly Clue media. The research method used was classroom action research in the form of four-stage cyclical learning, namely initial planning, implementation, observation, and reflection. The learning outcomes of students in pre-cycle learning that reached KKTP were 11 out of 24 students or less than 50%. In cycle I, the number of students who received cognitive assessments or learning outcomes reached KKTP was 15 students with a classical completion percentage of 66.67%. The cognitive value or learning outcomes of all students increased with a classical completion percentage of 100% with a score of ≥ 80 in cycle II. The implementation of the TGT cooperative model assisted by Cardopoly Clue media has been proven to maximize the active involvement of students which results in increased science learning outcomes.